2021
DOI: 10.1038/s41598-021-81768-6
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide, 7,8-DHF and their co-treatment prevents loss of vision and cognitive decline in a Wolfram syndrome rat model

Abstract: Wolfram syndrome (WS) is a monogenic progressive neurodegenerative disease and is characterized by various neurological symptoms, such as optic nerve atrophy, loss of vision, cognitive decline, memory impairment, and learning difficulties. GLP1 receptor agonist liraglutide and BDNF mimetic 7,8-dihydroxyflavone (7,8-DHF) have had protective effect to visual pathway and to learning and memory in different rat models of neurodegenerative disorders. Although synergistic co-treatment effect has not been reported be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 52 publications
8
41
0
Order By: Relevance
“…These results are in accordance with our previous observations, which showed that also short-term liraglutide treatment rescued ganglion cell density in Wfs1 KO rats (Seppa et al, 2019). Additionally, we found a consistent reduction of axonal area and number of axons in the optic nerve of Wfs1 deficient rats, accompanied by neuropathological signs of degeneration, ultimately resulting in optic nerve atrophy (Plaas et al, 2017;Seppa et al, 2019Seppa et al, , 2021. In the current study, we observed that the treatment with liraglutide was able to halt this neurodegeneration.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…These results are in accordance with our previous observations, which showed that also short-term liraglutide treatment rescued ganglion cell density in Wfs1 KO rats (Seppa et al, 2019). Additionally, we found a consistent reduction of axonal area and number of axons in the optic nerve of Wfs1 deficient rats, accompanied by neuropathological signs of degeneration, ultimately resulting in optic nerve atrophy (Plaas et al, 2017;Seppa et al, 2019Seppa et al, , 2021. In the current study, we observed that the treatment with liraglutide was able to halt this neurodegeneration.…”
Section: Discussionsupporting
confidence: 75%
“…Wfs1 KO rats develop a more prominent diabetic phenotype than any previously generated mouse model of WS and show neurodegeneration of the brainstem and optic nerve. As such, this rat model of WS recapitulates clinical findings observed in human patients and therefore provides an excellent model to evaluate pharmacological treatment strategies (Plaas et al, 2017;Seppa et al, 2019Seppa et al, , 2021Toots et al, 2018).…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations